Design and optimization of active solar Heating system subjected to Tripoli microclimate - G. E. A. Muftah; Nisreen Issa Aboujnah (African Journal of Advanced Pure and Applied Sciences, 2025)
In order to design liquid Solar Water Heating (SWH) Systems under Tripoli microclimate conditions, the typical correlation based methods incorporate with the f- chart method were employed. It is normally used this methods because of its capability to evaluate the heat load fraction provided by the solar heating system. This methods are perfect in optimizing the solar collectors area for standard Configuration for SWH system. The Combine f-chart with the LCS was utilized, to define the optimum design and cost of the system. In this study, the effect of collector orientation on the overall performance of SWH system was considered, alteration of a fraction of the total load provided by insolation energy and an optimum collector size for the desired load was founded. Detail information about solar radiation availability is required for design and economic evaluation of a solar energy system. Long-term solar radiation measurements for Tripoli city are available and can be obtained. In this work, we analyzed the solar energy resource potential for Tripoli in order to design a suitable and optimal solar flat plate collector for residential use. The purpose of this work is to design or size and optimize solar space and water heating system (active solar heating system) in order to convert solar energy into hot water and distribute it into the domestic proposes. For which, the microclimate of Tripoli will be analysed and the f-chart method is employed. Since the flat plate collector is expensive, the economic analysis is taken place. At the end , the size and parameters of solar heating system will be optimized for this particular location.